Are Western Iberian roe deer populations hotspots of genetic diversity? - Pereira, Jorge C. (2022)
Given its geographic isolation, and after the last glaciation, the Iberian Peninsula, become a sanctuary of plants and animal’s diversification, being considered a hotspot of genetic diversity specially for mammal species. The roe deer (Capreolus capreolus - CCR), an herbivore ungulate, has a widespread geographical distribution which extends from the Iberian Peninsula to the north of Scandinavia, being found as well in Turkey, Israel, and Jordan. C. capreolus populations have been subject to a significant number of fluctuations, especially due to anthropogenic activities, which led to a decrease in size and distribution. These alterations combined with translocations of animals of the same species, can lead to meaningful consequences on the genetic structure, diversity, and fitness of populations.